Outside the archives - "Gundevia, Y. D." (Hyderabad, 1984)
Outside The Archives(cc) The memoirs of a retired officer of the Indian Civil Service, this is an extremely informative and revealing book. In his 36 years of service, the author worked with many eminent politicians and diplomats in India and abroad. The central figure of the book is Pandit Jawaharlal Nehru, whom the author came into close contact with and with whom the author had a genuinely cordial working relationship for many years.
Keywords: India-history